-6(5-x)+3=3(x-1)

Simple and best practice solution for -6(5-x)+3=3(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(5-x)+3=3(x-1) equation:


Simplifying
-6(5 + -1x) + 3 = 3(x + -1)
(5 * -6 + -1x * -6) + 3 = 3(x + -1)
(-30 + 6x) + 3 = 3(x + -1)

Reorder the terms:
-30 + 3 + 6x = 3(x + -1)

Combine like terms: -30 + 3 = -27
-27 + 6x = 3(x + -1)

Reorder the terms:
-27 + 6x = 3(-1 + x)
-27 + 6x = (-1 * 3 + x * 3)
-27 + 6x = (-3 + 3x)

Solving
-27 + 6x = -3 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-27 + 6x + -3x = -3 + 3x + -3x

Combine like terms: 6x + -3x = 3x
-27 + 3x = -3 + 3x + -3x

Combine like terms: 3x + -3x = 0
-27 + 3x = -3 + 0
-27 + 3x = -3

Add '27' to each side of the equation.
-27 + 27 + 3x = -3 + 27

Combine like terms: -27 + 27 = 0
0 + 3x = -3 + 27
3x = -3 + 27

Combine like terms: -3 + 27 = 24
3x = 24

Divide each side by '3'.
x = 8

Simplifying
x = 8

See similar equations:

| j+2=-1 | | 7x-6=-13 | | -2u-18=0 | | 5-1-2x=12 | | 700x-35=450x+15 | | Z-38=-46 | | 3(5-x^2)-5= | | 2+k=-9 | | 1.8C+32=32.9 | | 11x-15y=23 | | -5-12+13p=11p-3 | | 8+3x=.5(16+16x) | | 10-6v=-94 | | 4j-5=150 | | -3k=31 | | 6=-7x+27 | | -6+12r=14r-20 | | 5(4+2x)=9(x-5) | | x-8.3=-5.3 | | 6a^2=a+12 | | 126=-9v | | 8-5n+2n=17-69 | | .5(10x-9)=5x+7 | | 0.5t+0.259(t+16)=4+0.75t | | 50-3x+15=2x | | 14x^2+86x+80=0 | | 8z-(3-z)=0 | | -113+5x=-6x+162 | | y+2x-1=5 | | 9(13-4)=81 | | 2w-11=3w-3 | | 43mg=5g |

Equations solver categories